Review of Micromachining of Ceramics by Etching - Chua, Han (National Core Research Center for Hybrid Materials Solutions Korea, 2008)
In the last two decades, there has been an enormous surge in interest in ceramic materials and, as a result there have been significant advances in their development and applications. Their inherent properties, such as capability of operating at temperatures far above metals, high level of hardness and toughness, low coefficient of thermal expansion and high thermal conductivity rendered ceramics to be one of the leading engineering materials. Many research works have been conducted in the past few years on machining of advanced ceramics using different processing methods in order to obtain a better surface roughness, higher rate of removal and improved tool life. Micromachining using chemical etching is one of those methods that do not involve the problem of tool life and direct tool-workpiece contact. However, only a few research works have been done on micromachining of ceramics using chemical etching.Hence, study of chemical machining of advanced ceramics is still needed as the process has found wide application in the industry because of its relative low operating costs. In this paper, we summarize the recent progresses in machining of different types of advanced ceramics, material processing methods such as wet etching and dry etching, and finally the prospects for control of material removal rate and surface quality in the process of ceramic micromachining.